Czy polski proces karny jest nadal procesem demokratycznym? - Katarzyna Dudka (Acta Iuris Stetinensis)
The legislator’s amendments made to the Code of Criminal Proceedings in Poland in the last few years have changed it tremendously, making it move away from the standards typical for the criminal trial of a democratic state of law. The article tries to answer the question of whether or not the Polish criminal trial is still democratic. A democratic trial is a trial fitting for a democratic rule of law. The article discusses the features of a democratic state ruled by law and, based on them, indicates factors that allow a criminal trial to be recognized as a rule-of-law trial. The study then presents examples of amendments made to the Code of Criminal Proceedings that have made the Polish criminal process cease to be democratic.